Assessment of Statin Utilization in the Republic of North Macedonia during 2013–2022 - Naumovska, Zorica; Nestorovska, Aleksandra K; Grozdanova, Aleksandra; Hristova, Kristina; Dimovski, Aleksandar; Suturkova, Ljubica; Sterjev, Zoran (Pharmaceutical Science: New Insights and Developments Vol. 3, 2025)
Aims: A rational use of statins has a major and increasing importance in public health and the allocation of financial resources by health insurance funds (HIFs). The aim of this study was to evaluate the market share and utilization trends of statins in the Republic of North Macedonia from 2013 to 2022. Study Design: A retrospective analysis and data comparison for the utilization of statins (C10AA) in the Republic of North Macedonia from 2013 to 2022 was conducted. Place and Duration of Study: The number of prescriptions for statins, pricing and reimbursement information for evaluation and comparative analysis of statin utilization were obtained from the official reports of the National Health Insurance Fund (NHIF). Methodology: The data for statin utilization were measured in defined daily doses per 1000 insurers per day (DDD/TID) in the period from 2013 to 2022. The unit prices were calculated per DDD according to the WHO Collaborative Center for Drug Statistics Methodology. Results: The total expenditure on prescription medications, including statins, is significant, with the NHIF allocating €45 million in 2022 for primary healthcare drugs, which represents a consistent upward trend since 2002. Cardiovascular drugs account for a major portion of these costs, making up 28% of the total drug expenditure. Statins, specifically atorvastatin and rosuvastatin, have been among the top prescribed medications, with rosuvastatin overtaking atorvastatin as the highest-cost statin from 2018 onward. Statin utilization, measured in Defined Daily Doses (DDD) per 1000 inhabitants per day (DDD/TID), has increased dramatically in the past years. From 42.35 DDD/TID in 2013, it rose to 71.7 DDD/TID in 2016 and reached 107.2 DDD/TID in 2022. Conclusion: To address these challenges, improving statin use, patient adherence, and healthcare provider education is essential. In North Macedonia, further efforts are needed to optimize statin therapy, reduce costs, and ultimately decrease CVD-related deaths.